(-3,4)x(-5,6)=
(-13,1)x(-0,3)=
12,8:(-4)=
(-9):2,25=
(-16,4):(-4,1)=
(-16,25):5=
(-12)+(-5)+2-(-12)=
17+8x(-3)=
(-15):(-3)-30:(-3)=
9-48:(-4)=
5-4x(-7+2)=
(-3)x4,5+(-3)x2,5=
(-2):4-16:2do potegi 3=
5 1/2:(5 1/2-2/5)+(5/6+3/4)x1 5/19=
-23,56+64,4:(-10)+

1

Odpowiedzi

2010-01-27T19:02:50+01:00
(-3,4)x(-5,6)= 19,04
(-13,1)x(-0,3)= 3,93
12,8:(-4)= 3,2
(-9):2,25= (-4)
(-16,4):(-4,1)= 4
(-16,25):5= (-3,25)
(-12)+(-5)+2-(-12)= (-3)
17+8x(-3)= (-7)
(-15):(-3)-30:(-3)= 15
9-48:(-4)= (-3)
5-4x(-7+2)= (-15)
(-3)x4,5+(-3)x2,5= (-21)
(-2):4-16:2do potegi 3= (-1,5)
5 1/2:(5 1/2-2/5)+(5/6+3/4)x1 5/19= 3 4/51
-23,56+64,4:(-10)= (-17,12)